Two new basal anomodont specimens from the Lower Abrahamskraal Formation (Beaufort Group: Karoo Supergroup) - implications for anomodont phylogeny and palaeoecology - Matlhaga, Fonda Ricardo (University of the Witwatersrand, Johannesburg, 2025)
Anomodontia is among the most prosperous therapsid clades in terms of abundance and diversity. Their largest subclade, the Dicynodontia, were present from the Middle Permian to the Late Triassic, reaching their maximum diversity during the Late Permian, before the end-Permian extinction event 252 million years ago. Basal anomodonts are known from South Africa, Russia, China, and Brazil. They are comparatively rare, and, as such, the earliest stages of anomodont evolutionary radiation remain obscure. Here, the cranial morphology of two new anomodont specimens from the Eodicynodon Assemblage Zone, lower Beaufort Group of South Africa are described: BP/1/8500 and BP/1/8740. The large size of BP/1/8500 makes it unique among early dicynodonts, and it combines features of both basal anomodonts and dicynodonts. Specimen BP/1/8500 is recovered as the second most basal dicynodont, stemwards to Nyaphulia oelofseni. In contrast, specimen BP/1/8740 is very small, and the large orbit and lack of canines are reminiscent of Patranomodon, Galechirus, and Galepus. A detailed description of this specimen indicates that it is a second specimen of Patranomodon and, most likely, a juvenile. This is supported by the phylogenetic analysis, which recovers it as a sister taxon to the holotype of Patranomodon. In addition, an analysis of body size suggests that anomodont body size has increased gradually over time while diversity decreased. Small-bodied anomodonts dominated before the end-Capitanian crisis, then large bodied anomodonts appeared during the Lopingian and went extinct at the end of the Permian. Anomodont size increased consistently during the Triassic, but the taxonomic diversity was extremely low. This supports that, as for many other tetrapod groups, large body size was a refugium niche for anomodonts as they approached extinction.
A dissertation submitted in fulfilment of the requirements of Master of Science, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Anomodont; Dicynodont; Chainosauria; Eodicynodon; Venyukovioidea; UCTD; SDG-15: Life on land; SDG-4: Quality education